GPS data from Brunt Ice Shelf close to the site of Halley VI Research Station from 2013 to August 2023 ... - Marsh, Oliver (NERC EDS UK Polar Data Centre, 2023)
GPS data recorded from three sites close to the 2023 site of Halley VI Research Station. Data from site LL20 spans 2013 to 2017; Data from site ZZ6A spans 2017 to 2023; Data from site ZMET spans 2022 to 2023. The data are presented as RINEX observation files. The data were collected as part of the Lifetime-of-Halley monitoring programme. This work was funded by NERC grant NE/X014991/1 (RIFT-TIP) and supported by NERC Antarctic Logistics and Infrastructure. ... : GNSS data is presented for ten consecutive years (2013-2023) from three sites on the Brunt Ice Shelf within the vicinity of the current Halley VI Research Station site. The GNSS at site LL20 recorded from 2013-2017. GNSS at ZZ6A recorded from 2017 onwards and was originally located approximately five kilometres east of the final position of LL20 (see paper for diagram). GPS only data from both sites were recorded in kinematic mode for two hours per day at 30-second intervals using a dual-frequency Leica GS10. (For 2018, the ZZ6A GNSS was a Leica GX1220.) The instrument at site ZMET was located approximately 500 m west of ZZ6A and recorded from 2022 onwards for 24-hours per day at one-second intervals, using an MB100 chip. ...